Actor experience: Bridging individual and collective-level theorizing - Becker Larissa; Karpen Ingo Oswald; Kleinaltenkamp Michael; Jaakkola Elina; Helkkula Anu; Nuutinen Maaria (Elsevier Inc., 2025)
Many marketing phenomena involve a group’s collective experiences; however, marketing research largely focuses on an individual’s experiences. This research argues that individual-level theorizing alone is inadequate to capture collective experiences, such as how families, teams, or business customers experience good and/or services. This article thus aims to conceptualize actor experience as encompassing both individual and collective experiences. We draw on S-D logic and phenomenology to describe how experience emerges for individual and collective actors. We then demonstrate the application of our conceptualization by informing a central marketing notion: the determination of value. More specifically, we delineate two types of value determination, value experience and value attribution, and discuss how social interaction and institutional factors influence them. This study contributes to marketing literature with the conceptualization of actor experience that can be applied to the study of collective phenomena and to S-D logic metatheory by advancing the understanding of value determination.